Pengaruh Brand Awareness dan Kualitas Produk Terhadap Keputusan Pembelian Pada NF Store Metro - Apriliani Putri; Hepiana Patmarina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
In an era of increasingly fierce business competition, a company's success is determined not only by the quality of its products but also by the strength of its brand in the minds of consumers. This study aims to determine the effect of Brand awareness and Product Quality on Purchasing Decisions at NF Store Metro. This study uses a quantitative approach with a causal associative research method. The population used in this study was all 4,000 NF Store Metro customers, with a sample size of 98 consumers. The data analysis methods used were validity testing, reliability testing, normality testing, multicollinearity testing, multiple linear regression analysis, t-test, and F-test. The Brand awareness variable (X1) has a regression coefficient of 0.205 with a significance value of 0.076 (>0.05). This indicates that Brand awareness (X1) has a partial positive effect on Purchase Decisions (Y). The Product Quality variable (X2) has a regression coefficient of 0.178 with a significance value of 0.149 (>0.05). This indicates that Product Quality (X2) also has a partial positive effect on Purchase Decisions (Y).